2016
DOI: 10.1007/s00267-016-0760-9
|View full text |Cite
|
Sign up to set email alerts
|

Look Who’s Talking. Explaining Water-Related Information Sharing and Demand for Action Among Ugandan Villagers

Abstract: Many national water policies propagate community-based participatory approaches to overcome weaknesses in supply-driven rural water provision, operation, and maintenance. Citizen involvement is thought to stimulate bottom-up accountability and broaden the information base, which may enrich design and implementation processes and foster improved water accessibility and sustainability. Practices on the ground, however, are embedded in socio-political realities which mediate possible beneficial effects of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Women Are the Primary Water Purveyors, Particularly in the Developing Regions of the World Largely, the identified observational studies ( Table 1) emphasized issues in accessing clean water among women and girls, and described that a lack of clean water and water resources negatively contributed to women and girl's health and quality of life (Doherty et al, 2007;Bornman et al, 2012;Sato et al, 2016;Gaspar et al, 2017;Vos et al, 2017;Angoua et al, 2018;Prado et al, 2019). Studies which considered gender likewise revealed a lack of access to improved water for both men and women alike (Ugbomoiko et al, 2009;Al-Delaimy et al, 2014;Atalabi et al, 2016;Holvoet et al, 2016;Akombi et al, 2017;Baker et al, 2018). Few studies directly compared whether access to water differed as a result of a gender.…”
Section: Synthesized Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Women Are the Primary Water Purveyors, Particularly in the Developing Regions of the World Largely, the identified observational studies ( Table 1) emphasized issues in accessing clean water among women and girls, and described that a lack of clean water and water resources negatively contributed to women and girl's health and quality of life (Doherty et al, 2007;Bornman et al, 2012;Sato et al, 2016;Gaspar et al, 2017;Vos et al, 2017;Angoua et al, 2018;Prado et al, 2019). Studies which considered gender likewise revealed a lack of access to improved water for both men and women alike (Ugbomoiko et al, 2009;Al-Delaimy et al, 2014;Atalabi et al, 2016;Holvoet et al, 2016;Akombi et al, 2017;Baker et al, 2018). Few studies directly compared whether access to water differed as a result of a gender.…”
Section: Synthesized Findingsmentioning
confidence: 99%
“…However, Bisung and Elliott (2018) showed that female-headed households had reduced access to water security (Bisung and Elliott, 2018). Moreover, within a household, there was substantial evidence that women as the primary carriers of water with prevalence estimates ranging from 61 to 79% (Hunter, 2006;Bornman et al, 2012;Holvoet et al, 2016;Geere et al, 2018). Indeed, the presence of a wife in the household significantly increased the likelihood of having access to clear water (Angoua et al, 2018).…”
Section: Synthesized Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to information: Disseminating information in a clear and understandable manner (e.g., by posters and information leaflets in public places) is essential to facilitate people's engagement in decision-making processes (e.g., budget monitoring) [118]. Mobilization and awareness raising: Awareness raising contributes effectively to increase participation of specific groups, particularly since people lacking access to clean water are those who are less likely to seek support [119].…”
Section: Use Of Local Knowledgementioning
confidence: 99%